Peran Pemerintah Daerah Kabupaten/Kota Dalam Pengawasan Tenaga Kerja Asing di Indonesia - La ode Dedihasriadi (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia implies that the natural resources which belong to the State are used for the prosperity of the people of Indonesia. Thus, in carrying out the mandate of the Constitution to create justice for the community and national economic development of employment including foreign workers, the government should provide a good mechanism and supervision so that there will be no gap between the mandate of the constitution and the acceleration of economic development involving foreign workers. Labor inspection done by a separate working unit in the agency whose scope of duties and responsibilities is in the field of employment is in the central government, provincial government, and district/ city government. This study used a normative-empirical approach, where the researcher examined the law and its implementation regarding the roles of district/ city governments in the supervision of foreign workers. The purpose of this study was to examine the extent of the roles of district/ city governments in overseeing foreign workers in their regions. The results of the study showed that the roles of district/ city governments in carrying out the supervision of foreign workers in Indonesia were not regulated by laws of No. 23 of 2014 concerning regional government, PP No. 20 of 2018 concerning the use of foreign workers, and Minister of Manpower Regulation No.10 of 2018 concerning procedures for the use of foreign workers. Thus, its implementation made it difficult for district/ city governments to oversee the presence of foreign workers in their areas.